American Fashion Influence in Japanese Imagination: A Study of Semiotic on Furudate’s Haikyuu!! - Fajarwati, Diah Prima; Adi, Ida Rochani (Pengkajian Amerika, Universitas Gadjah Mada, 2024)
This research discusses the influence of American culture in Japan on Haruichi Furudate's Haikyuu!! manga. The manga was published in 2012 and ended in 2020 with 45 volumes. In the context of American influence, more precisely in the field of sports, one of them is adopted as the theme of the Haikyuu!! manga, which is volleyball. This manga tells the journey and struggle of the main character, Hinata Shoyo, to become a professional volleyball athlete. But as it turns out, apart from the volleyball sport introduced by America, there are other aspects that are also American influences. By using Transnational American Studies, this research found the influence of American culture by the characters in the Haikyuu!! manga. The influence of American culture in this research is specific to the cultural aspect, fashion, which is then examined using the semiotics of Roland Barthes. From the analysis, it was found that there is some American fashion used by some characters in Haikyuu!! manga, leather jacket and denim.